Adverbs of Manner and Its Translation Found in The Novel “Edensor” - Maria Osmunda Eawea Monny (Austronesian: Journal of Language Science & Literature, 2022)
This study aims to analyze the translation of adverbs of manner and its’ translation techniques of adverb of manner from Indonesian as the source language to English as the target language. Adverbs are words that modify verbs, adjectives, and other adverbs, and in English, they mostly come in the form of -ly. The theory used in this study is the theory of Brown and Miller (1992). It is a descriptive qualitative study that takes data from the novel Edensor. The data is collected and analyzed based on its form, for example, from verbs, adjectives, or adverbs. The results of this study show that out of 75 data, there were 35 data from adjectives, 19 data from adverbs, 17 data from reduplications, and 2 data from verbs. The translation word categories used were (1) adjective in Indonesia to be adverb -ly, (2) reduplication in Indonesia to be adverb -ly, and (3) adverbs in Indonesia to be adverb -ly. Furthermore, the translation techniques were transposition, modulation, and literal.